Strategi Pemberdayaan UMKM melalui Digitalisasi Keuangan untuk Keberlanjutan Bisnis - Yuli Ermawati; Pujianto Pujianto; Endah Supeni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
. This study aims to explore Micro, Small, and Medium Enterprises (MSME) empowerment strategies through financial digitalization using a descriptive qualitative approach. Specifically, the study seeks to describe MSMEs’ perceptions and experiences regarding financial digitalization, identify the supporting and inhibiting factors influencing its implementation, and formulate effective empowerment strategies based on digital financial practices. Data were collected through in-depth interviews with MSME owners, MSME facilitators and academics, as well as representatives from the Surabaya City Cooperatives, MSMEs, and Trade Office. The findings reveal that financial digitalization provides significant opportunities for MSMEs to improve financial management, increase operational efficiency, and expand access to financial services. However, several challenges remain, including limited digital financial literacy, inadequate technological skills, resistance to change, and infrastructure constraints. The study also finds that successful financial digitalization requires continuous mentoring, user-friendly accounting technologies, strong collaboration among government institutions, academics, financial institutions, and business communities, as well as efforts to strengthen digital financial literacy. Based on these findings, the study proposes a digital-based MSME empowerment model that emphasizes gradual technology adaptation, behavioral transformation in financial management, and sustainable stakeholder support to enhance MSME competitiveness and long-term growth